Tangential Field Radiotherapy for Breast Cancer—The Dose to the Heart and Heart Subvolumes: What Structures Must Be Contoured in Future Clinical Trials? - Duma, Marciana Nona; Herr, Anne-Claire; Borm, Kai Joachim; Trott, Klaus Rüdiger; Molls, Michael; Oechsner, Markus; Combs, Stephanie Elisabeth (Frontiers in Oncology, 2017)
Background and purpose The aim of the present study was to evaluate if it is feasible for experienced radiation oncologists to visually sort out patients with a large dose to the heart. This would facilitate large retrospective data evaluations. And in case of an insufficient visual assessment, to define which structures should be contoured and which structures can be skipped as their dose can be derived from other easily contoured structures for future clinical trials. Material and methods Planning CTs of left-sided breast cancer patients treated with 3D-conformal radiotherapy by tangential fields were visually divided into two groups: with an estimated high dose (HiD) and with an estimated low dose (LoD) to the heart. For 46 patients (22 HiD and 24 LoD), the heart, the left ventricle, the left anterior descending artery (LAD), the right coronary artery, and the ramus circumflexus were contoured. A helper structure (HS) around the LAD was generated in order to consider if contouring uncertainties of the LAD could be acceptable. We analyzed the mean dose (Dmean), the maximum dose, the V10, V20, V30, V40, and the length of the LAD that received 20 and 40 Gy. Results The two groups had a significant different Dmean of the heart (p < 0.001). The average Dmean to the heart was 4.0 ± 1.3 Gy (HiD) and 2.3 ± 0.8 Gy (LoD). The average Dmean to the LAD was 26.2 ± 7.4 Gy (HiD) and 13.0 ± 7.5Gy (LoD) with a very strong positive correlation between Dmean LAD and Dmean HS in both groups. The Dmean heart is not a good surrogate parameter for the dose to the LAD since it might underestimate clinically significant doses in 1/3 of the patients in LoD group. Conclusion A visual assessment of the dose to the heart could be reliable if performed by experienced radiation oncologists. However, the Dmean heart is not always a good surrogate parameter for the dose to the LAD or for the Dmean to the left ventricle. Thus, if specific late toxicities are evaluated, we strongly recommend contouring of the specific heart substructures as a heart Dmean is not highly specific.